Biased signaling by mutant EGFR underlies dependence on PKCα in lung adenocarcinoma - Mojtaba Sadeghi; Mohamed F. Salama; Sam B. Chiappone; Amy Huang; Andrew E. Resnick; Manoj Kandpal; Christopher J. Clarke; John D. Haley; Ramana V. Davuluri; Yusuf A. Hannun (Cell Reports)
Summary: Activating mutations in the epidermal growth factor receptor (EGFR) promote ligand-independent signaling; however, the mechanisms involved are poorly defined, and it is unknown whether this generates specific vulnerabilities. We previously observed robust expression of protein kinase Cα (PKCα) in lung adenocarcinoma (LUAD) with mutant EGFR (mEGFR), which, unlike the activation of PKCα, is independent of mEGFR activity. Here, we identify a critical role for PKCα in anchorage-independent growth and survival of lung cancer cells with mEGFR. Mechanistically, signaling pathways initiated by mEGFR show a high preference for ligand-independent phosphorylation on Y992, resulting in biased activation and dependence on phospholipase-Cγ and PKCα. Moreover, through bioinformatic approaches, we find that mEGFR LUAD demonstrates a transcriptomic profile most similar to lung basal cells, which exhibit elevated levels of PKCα, suggesting that mEGFR tumors arise in cell types with high intrinsic levels of PKCα. Taken together, these findings explain the dependence of mEGFR on PKCα.